Privatizing criminal stigma: Experience, intergroup contact, and public views about publicizing arrest records. (July 2019) - Lageson, Sarah E; Denver, Megan; Pickett, Justin T
Current U.S. policy allows private companies to publish arrest records prior to conviction in print and online sources, yet little is known regarding the extent to which people actively search for criminal records or whether the public supports these policies. Utilizing two large public opinion surveys (N = 1008 and N = 1601), we find that approximately 15% of Americans searched online for conviction records last year (an estimated 38 million people), but that a strong majority (88%) oppose the publication of arrest records by private companies. We measure correlates of opposition to record disclosure and find that having high-quality interpersonal contact with an arrestee diminishes support for publicizing arrest records and also tempers views of recidivism risk for those with nonviolent convictions. Findings suggest that learning firsthand about the negative consequences of contemporary criminal labels changes popularly held views on the value of immediate arrest record disclosure.